2022
DOI: 10.1017/s0954579422000499
|View full text |Cite
|
Sign up to set email alerts
|

A review of mental health disparities during COVID-19: Evidence, mechanisms, and policy recommendations for promoting societal resilience

Abstract: Social and economic inequality are chronic stressors that continually erode the mental and physical health of marginalized groups, undermining overall societal resilience. In this comprehensive review, we synthesize evidence of greater increases in mental health symptoms during the COVID-19 pandemic among socially or economically marginalized groups in the United States, including (a) people who are low income or experiencing homelessness, (b) racial and ethnic minorities, (c) women and lesbian, gay, bisexual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 238 publications
0
28
0
Order By: Relevance
“…Previous studies showed that job insecurity and job loss are strongly related to depression and anxiety and to a lesser extent to emotional exhaustion (Rönnblad et al 2019 ; Niedhammer et al 2021 ). A recent review indeed showed higher levels of depression symptoms during the COVID-19 pandemic among those with a lower income (Parenteau et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that job insecurity and job loss are strongly related to depression and anxiety and to a lesser extent to emotional exhaustion (Rönnblad et al 2019 ; Niedhammer et al 2021 ). A recent review indeed showed higher levels of depression symptoms during the COVID-19 pandemic among those with a lower income (Parenteau et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic precipitated an overall increase in the global prevalence of mental health disorders and psychological distress. Pronounced increases in depressive symptoms, fear and anxiety, loneliness, and stress were documented in various countries and across diverse population groups (e.g., [ 2 , 3 , 36 ]). However, against this backdrop, there was also evidence of adaptation and coping, which suggested the influence of protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…Public health responses to the COVID-19 pandemic, including national lockdowns, restrictions on travel, closure of educational institutions, and stay-at-home orders, have disrupted the lives of people on a global scale [ 1 ]. Recent studies have confirmed that these pandemic-related stressors and the associated life changes lead to serious psychological distress and common mental health disorders, including increased loneliness and anxiety [ 2 , 3 ]. Loneliness is defined as a distressing emotional state arising from an unmet need for social connection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has illustrated the remarkable collective resilience of individuals coming together as a community through the common experience of crisis. The factors commonly recognized as having had an impact on collective resilience in the face of the pandemic include collective efficacy, social leadership and fairness, racial or ethnic identity, policies and cultural forms, faith and social connection, flexibility, and social cohesion [ 20 , 28 , 29 , 30 , 31 , 32 ]. Social cohesion includes trust, a sense of belonging, social interactions and engagement [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%